2012
DOI: 10.1016/j.neurobiolaging.2010.07.020
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ApoE4 and maternal history of dementia on hippocampal atrophy

Abstract: We applied an automated hippocampal segmentation technique based on adaptive boosting (AdaBoost) to the 1.5T MRI baseline and 1-year follow-up data of 243 subjects with mild cognitive impairment (MCI), 96 with Alzheimer's disease (AD) and 145 normal controls (NC) scanned as part of the Alzheimer's Disease Neuroimaging Initiative (ADNI). MCI subjects with positive maternal history of dementia had smaller hippocampal volumes at baseline and at followup, and greater 12-month atrophy rates than subjects with negat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
42
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 62 publications
(74 reference statements)
5
42
1
1
Order By: Relevance
“…These data are consistent with epidemiologic and biomarker findings that maternal transmission is associated with higher risk than paternal transmission, independent of increased female longevity. 2,11,[13][14][15][16][17][18][26][27][28][29][30][31] Present findings expand on prior unimodality biomarker studies showing multiple biomarker deficits in NL FHm, which appeared to be overall less severe than in FHmp. Interestingly, NL FHm was the only group in which Ab load did not significantly exceed hypometabolism.…”
Section: Statistical Analysis Spss Version 19 (Ibm Corp Armonk Ny)supporting
confidence: 77%
See 2 more Smart Citations
“…These data are consistent with epidemiologic and biomarker findings that maternal transmission is associated with higher risk than paternal transmission, independent of increased female longevity. 2,11,[13][14][15][16][17][18][26][27][28][29][30][31] Present findings expand on prior unimodality biomarker studies showing multiple biomarker deficits in NL FHm, which appeared to be overall less severe than in FHmp. Interestingly, NL FHm was the only group in which Ab load did not significantly exceed hypometabolism.…”
Section: Statistical Analysis Spss Version 19 (Ibm Corp Armonk Ny)supporting
confidence: 77%
“…It remains to be established whether Ab accumulation is also an early event in LOAD. 1 Previous brain imaging studies have shown that, among NL individuals who have parents with LOAD, those with maternal FH (FHm) present with increased Ab load on 11 C-Pittsburgh compound B (PiB)-PET, 11,12 progressive glucose metabolism reductions on 18 F-fluoro-2-deoxyglucose (FDG)-PET, 13,14 and gray matter volume (GMV) loss on MRI [15][16][17][18] in the same regions as those with clinical AD. In contrast, NL individuals with paternal FH (FHp) are far less likely to show biomarker abnormalities.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…25,26 Moreover, a recent study of family history in the ADNI sample found a significant effect of positive maternal history of dementia on hippocampal atrophy in individuals with MCI and AD, independent of age and APOE4. 27 While we did not identify any differences in hippocampal atrophy between FH groups, our parahippocampal atrophy finding in the FHm group is in close proximity. Our results complement several studies showing progressive temporal and parietal hypometabolism in FHm individuals over time.…”
Section: Resultscontrasting
confidence: 58%
“…In addition, APOE-rs429358 has been shown to be related to medial temporal lobe atrophy [31], hippocampal atrophy [32] and cortical atrophy [33]. Variants within membrane-spanning 4-domains subfamily A (MS4A) gene cluster are some other recently discovered AD risk factors [34].…”
Section: Resultsmentioning
confidence: 99%